2018
DOI: 10.1093/mnrasl/sly127
|View full text |Cite
|
Sign up to set email alerts
|

Coronal EUV, QFP, and kink waves simultaneously launched during the course of jet–loop interaction

Abstract: We present the observations of an extreme ultraviolet (EUV) wave, a quasi-periodic fast-propagating (QFP) magnetosonic wave, and a kink wave that were simultaneously associated with the impingement of a coronal jet upon a group of coronal loops. After the interaction, the coronal loop showed obvious kink oscillation that had a period of about 428 seconds. In the meantime, a large-scale EUV wave and a QFP wave are observed on the west of the interaction position. It is interesting that the QFP wave showed refra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 50 publications
1
23
0
2
Order By: Relevance
“…Observational studies indicated that solar jets can act as a driver to excite torsion Alfvén waves in themselves (see §2d(iii)), kink waves in remote coronal loops and filaments, and large-scale EUV waves. Statistical analysis indicated that the most probable mechanism for exciting kink oscillations in coronal loops is the deviation of loops from their equilibrium by nearby eruptions of plasma ejections [223,224]. Using the magneto-seismology technique, the measured oscillation parameters could be used to derive the magnetic field strength of the loops/filaments.…”
Section: (C) Magnetohydrodynamic Wavesmentioning
confidence: 99%
“…Observational studies indicated that solar jets can act as a driver to excite torsion Alfvén waves in themselves (see §2d(iii)), kink waves in remote coronal loops and filaments, and large-scale EUV waves. Statistical analysis indicated that the most probable mechanism for exciting kink oscillations in coronal loops is the deviation of loops from their equilibrium by nearby eruptions of plasma ejections [223,224]. Using the magneto-seismology technique, the measured oscillation parameters could be used to derive the magnetic field strength of the loops/filaments.…”
Section: (C) Magnetohydrodynamic Wavesmentioning
confidence: 99%
“…QFP波时常在传播过程中表现出明显的波动效 应. 比如, 与强磁场结构作用发生明显的折射效应进而 改变传播方向 [23,94] ; 沿闭合磁力线传播时, 波前在磁力 线另一端被反射并导致闭合磁环的振荡等 [19,45,133] .…”
Section: Qfp波最早出现位置离耀斑中心的距离通常>100unclassified
“…大多数QFP波的激发可能与引发耀斑的磁重联 过程中的非线性物理过程密切相关 [21,23,25,137,139] , 例如 电流片中等离子体团的分裂、合并和喷射 [140,141] 以及 振荡重联等 [142] . 同时, 部分观测结果显示, 太阳爆发扰 动在非均匀介质中通过色散式演化 [24,94,95] , 而光球压 力模向上泄漏到日冕 [21,22]…”
Section: 荡相关 不会激发准周期波; 而其余3种机制都可激发unclassified
“…It is well known that various of solar activities are closely associated with solar magnetic field processes and the study of the long-term evolution of solar activities are useful for the understanding of the solar atmosphere and the dynamo theories (e.g., [1][2][3][4]). e sunspot numbers (SSN), being the most important index of the solar activities, have been widely studied together with other indices [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%